International e-marketing - Krishnamurthy, Sandeep, 1967-; Singh, Nitish (International marketing review, 2005)
The internet, web and related information technologies have proven to betransformational. While these technologies have impacted all parts of the corporation,the marketing function has perhaps been most affected. E-marketing is now a significantpart of every global corporation's marketing arsenal. As international acceptance of theinternet and web increases, the scope of international e-marketing now transitions frompossibility to reality.International marketing scholars have followed the transformational impact of theinternet/web closely. Several studies in the international e-marketing conte.